2019
DOI: 10.21744/irjeis.v5n1.596
|View full text |Cite
|
Sign up to set email alerts
|

The effect of love of money and emotional intelligence on employee performance with organizational citizenship behavior as mediating variable

Abstract: The variables used in this study design are the first exogenous variables (exogenous) a love of money, organizational citizenship behavior, and emotional intelligence. Endogenous variables (endogenous) are employee performance. The population in this study were all employees in 51 BPRs in Badung Regency in 2018 where the returned questionnaires were 117. Data analysis in this study used the Partial Least Square (PLS) approach using SmartPLS software. The results of this study are, 1) Love of money has a negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
3
11
0
3
Order By: Relevance
“…This study showed a significant relationship between emotional intelligence and UCB and its different dimensions. This is identical to the results observed concerning the relationship between OCB and Emotional Intelligence in West, India, and Far-East (e.g., Vandewaa et al, 2016;Sharma &Mahajan, 2017;Widiani et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed a significant relationship between emotional intelligence and UCB and its different dimensions. This is identical to the results observed concerning the relationship between OCB and Emotional Intelligence in West, India, and Far-East (e.g., Vandewaa et al, 2016;Sharma &Mahajan, 2017;Widiani et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Miao et al(2017) viewed that Emotional Intelligence may help to motivate employees as it is related to empathy and in their meta-analysis opined that considerable literature has related EI to Empathy. Widiani, Putri, Sari, and Wirajaya (2019) based on their study in Bali, Indonesia opined when an employee has high intelligence, he/she shows more love for the Company through organizational citizenship behaviour. This logic holds good particularly for the conscientiousness dimension of UCB as the students with high emotional intelligence display their love for the University by projecting its good image to the society and walking the extra mile for the benefit of the university.…”
Section: Malaysian Online Journal Of Educational Management (Mojem)mentioning
confidence: 99%
“…The research of Arshadi & Damiri (2013), produces empirical evidence of the positive influence of role stress on turnover intentions. The results of this study are supported by the research of Pradana & Salehudin 2015 Pant et al, (2016); Widiani et al, (2019), which prove the existence of a positive relationship with role stress on turnover intentions. The high level of stress felt by tax consultants will have an impact on decreasing job satisfaction and work discomfort which will lead to turnover intentions.…”
Section: The Effects Of Role Stress On Turnover Intentionssupporting
confidence: 80%
“…Uang merupakan salah satu faktor yang mempengaruhi perilaku etis seseorang. Sifat manusia menyebabkan seseorang cenderung selalu memiliki keinginan yang tidak pernah puas dalam suatu pencapaian termasuk keinginan untuk pencapaian finansial (Widiani et al, 2019). Love of money mampu mempengaruhi sifat dari professional akuntan (Sipayung & Cahyonowati, 2015).…”
Section: Pendahuluanunclassified